Neurophysiologic evaluation of workers in an automotive body repair center - Tigno, Xenia T.
Fifty-two workers from two automotive service centers in Metro Manila were examined for signs and symptoms of neurotoxicity and compared with fifty-three security guards from two security agencies also in Metro Manila. Tests performed included the standard neurological and physical examinations, a Subjective Symptoms Questionnaire, the Digits Forward and Digits Backward Tests, the Digit Symbol Test, the Pursuit Aim Test, and Simple Reaction Time. In addition, a detailed personal and occupational history was taken. Average length of employment in the automotive industry was 6.43 ? 4.9 years. The neurological examination failed to reveal any adverse effect of employment in the auto service center on neurological function. Reflexes of the auto workers were significantly faster than those of the guards. Heart rate was significantly lower among the security guards, but upon multiple regression analysis, exposure was not a significant predictor of heart rate. In the neurophysiological tests, the auto workers performed significantly better in the Digit Forward test and exposure was a significant predictor, based on multiple regression analysis. In the simple reaction time, the automotive workers demonstrated shorter latency of response, which was consistent with the findings of faster reflexes. This may be either be due to the training in the auto industry which requires manipulative skills and agility, or to presence of sleep deprivation among the security guards. The subjective symptoms score among the auto workers was higher than those of the security guards, but the difference was not significant. Only contact dermatitis was significantly more prevalent among the auto workers than among the comparison group. Therefore, based on the tests performed in the study, exposure to the environmet in the auto service center did not produce any statistically or clinically significant adverse effect on the neurophysiological function of the exposed workers.
Thesis (Master of Science in Epidemiology)--University of the Philippines Manila.
Keywords: Neurotoxicology; Industrial hygiene